2007
DOI: 10.1590/s1516-635x2007000200001
|View full text |Cite
|
Sign up to set email alerts
|

Breeder nutrition and offspring performance

Abstract: Vertical integration in poultry industry strongly emphasizes the importance of cost control at all levels. In the usual broiler production operations, the costs involved with the production of the hatching egg or the day old chick are negligible if seen in the perspective of the cost per kg of live bird.From a research point of view, anyway, the greatest attention is usually given to the performance of broiler breeders, and most of the research in the field is focused on the improvement of their relative perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
0
26
0
2
Order By: Relevance
“…The nutrients required for chicken embryo development are derived from the nutrients stored in the egg, whose nutrient profile changes with the maternal diet and thereby creates differences in nutritional status of offspring (Calini and Sirri, 2007). Peebles et al (2002) showed that the type of fat that is included in the maternal diet affects the body composition of offspring at the age of slaughter.…”
Section: Resultsmentioning
confidence: 99%
“…The nutrients required for chicken embryo development are derived from the nutrients stored in the egg, whose nutrient profile changes with the maternal diet and thereby creates differences in nutritional status of offspring (Calini and Sirri, 2007). Peebles et al (2002) showed that the type of fat that is included in the maternal diet affects the body composition of offspring at the age of slaughter.…”
Section: Resultsmentioning
confidence: 99%
“…The requirements of broiler breeder hens for specific immunomodulatory nutrients and their impact on the health, and consequently the production of broiler chickens, also need to be continually reviewed because of the rapid genetic changes (Calini & Sirri, 2007).…”
Section: The Effect Of Arginine Dietary Supplementation In Broiler Brmentioning
confidence: 99%
“…Considering a breeder produces 130-140 chicks during its life time, small variations in breeder performance resulting from better nutrient intake have an important impact on farm profitablity (Calini & Sirri, 2007).…”
Section: Introductionmentioning
confidence: 99%